Effect of Pumpkin Cream Soup on Blood Glucose in Type 2 Diabetes Outpatients in North Aceh - Amelia, Riski; Junita, Dini (JAND: Journal of Applied Nutrition and Dietetic, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels (hyperglycemia). One innovative dietary approach to help manage hyperglycemia is the consumption of pumpkin cream soup. Pumpkin is rich in beta-carotene, flavonoids, vitamin C, and soluble fiber such as pectin, and also contains various bioactive compounds including proteins, peptides, polysaccharides, sterols, and para-aminobenzoic acid. This study aimed to determine the effect of pumpkin cream soup on blood sugar levels in type II diabetes mellitus outpatients at the UPTD Muara Batu Health Center, North Aceh Regency. A quasi-experimental design with a one-group pretest-posttest approach was employed. The intervention was conducted over seven consecutive days, which participants consumed pumpkin cream soup daily. Blood glucose levels were measured using the Easy Touch glucometer before and after the intervention. Data were analyzed using the paired sample t-test. The results showed that the average fasting blood glucose level decreased from 189.65 mg/dL before the intervention to 167.00 mg/dL after, with an average reduction of 22.65 mg/dL. The findings indicate a significant effect of pumpkin cream soup consumption in lowering blood sugar levels among type II diabetes mellitus patients. Therefore, pumpkin cream soup may be recommended as a dietary alternative to help manage blood glucose levels in individuals with type II diabetes mellitus.